(3bQI GdYjf aj GdaJM hGdEeGdI Hjf GddaXjfs - (3Ydj Hf YKeGf Hf eMeO Hf CMeO, CHh GdHbGA GdYPQj, hjYQa H (B: (3GHf GdbGUM,J (B801 (3g` s
(3ChdgG (B:s
(3bGd CHh GdHbGA Ydi Hf YKeGf CeG HYO MeO QH GdYGdejf aEf gPg QSGdI SejJgG HbQI GdYjf hLeYI ajgG GdeTghQ ef GdaJM hGdEeGdI hHjf GddaXjf eeG bQCJ Hg hQhjJg Yf GdCFeI GdSHYI s
(3BNQgG (B:s
(3hShQI GdfGS HQH GdfGS edc GdfGS Zdg GdfGS UOhQ GdfGS GdLedI NeS cdeGJ PcQ GdHbQI gPG BNQ GdcJGH GdeSei HbQI GdYjf hHGddg GdJhajb hgh MSHi hfYe Gdhcjd hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg CLeYjf JeJ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ YfGhjf GdCHhGH hGdShQ hGdahGJM HGdMeQIs
(3fSNI eUMMI s
(3fSNI ecQQI hdcfgG CaVd ef GdSGHbI s
(3bQf GdfSN (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs